A arquitetura do Império Romano: uma discussão das construções da Bitínia na correspondência entre Plínio, o Jovem e Trajano - Costa, Alex Aparecido da (Romanitas - Revista de Estudos Grecolatinos, 2021)
One of the important aspects of cohesion in the Roman Empire was urbanism. Cities were spaces for the affirmation of the Roman social order, above all for its ruling layers. In the provinces, the administration, through a pact with the elites, promoted construction that supported local power and imperial power. Outstanding expressions of the integration processes of the Roman Empire, these efforts were marked by the complexity of power relations between the center and the periphery of the Roman world. In this article we will discuss the presence of these elements in the letters of Pliny the Younger and Trajan about the administration of the Roman province of Bithynia.